Applying computational linguistic and text analysis to media content about migration - Allen, WL (British Academy, 2023)
As larger and more varied datasets on socially and political relevant issues have become available to researchers, computational methods that aim to make sense of them have also proliferated. In response, social scientists need to critically reflect on and take stock of the opportunities and challenges presented by these shifts. This chapter draws upon on a series of projects that involved collecting, analysing, and communicating results from a large corpus of British newspaper texts about migration, asylum-seekers, and refugees spanning 1985-2015. By reporting the choices I made during these steps, as well as the contexts in which they happened, I aim to draw out both theoretical and practical lessons for researchers wanting to use computational approaches to media data involving political topics like migration—particularly, but not exclusively, from linguistic perspectives.